2015
DOI: 10.1186/s13567-015-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β superfamily members from the helminth Fasciola hepatica show intrinsic effects on viability and development

Abstract: The helminth Fasciola hepatica causes fasciolosis throughout the world, a major disease of livestock and an emerging zoonotic disease in humans. Sustainable control mechanisms such as vaccination are urgently required. To discover potential vaccine targets we undertook a genome screen to identify members of the transforming growth factor (TGF) family of proteins. Herein we describe the discovery of three ligands belonging to this superfamily and the cloning and characterisation of an activin/TGF like molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…We have recently shown that the trematode parasite Fasciola hepatica contains three ligand members of the transforming growth factor superfamily [17]. These include two bone morphogenic proteins (BMPs) and an activin-like molecule which we have terms F .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that the trematode parasite Fasciola hepatica contains three ligand members of the transforming growth factor superfamily [17]. These include two bone morphogenic proteins (BMPs) and an activin-like molecule which we have terms F .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that FhTLM is selectively expressed within the newly excysted juvenile (NEJs) stage of F. hepatica infection [17]. NEJs are thought to be resident within the intestine for only a number of hours before entering the peritoneal cavity and continuing on their migration to the liver.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations